Serum albumin-carcinoembryonic antigen ratio as an effective clinical tool for predicting recurrence and overall survival in patients with rectal cancer - Xie, Hailun; Wei, Lishuang; Tang, Shuangyi; Gan, Jialiang (Frontiers in Nutrition, 2025)
BackgroundThe albumin–carcinoembryonic antigen ratio (ACR), leveraging the strengths of albumin and CEA, has emerged as a promising serum prognostic marker. However, no studies to date have explored the association between ACR and the prognosis of patients with rectal cancer. This study aimed to determine the value of albumin–carcinoembryonic antigen ratio (ACR) in predicting the progression-free survival (PFS) and overall survival (OS) of patients with rectal cancer.MethodsSurvival analysis was conducted using the Kaplan–Meier method, and hazard ratios (HR) were calculated using Cox regression analyses. Nomograms were created based on variables with p < 0.05 in the multivariate Cox regression analysis. The predictive ability of the model was evaluated using the C-index and calibration curve, and its prognostic predictive abilities were compared to those of traditional Tumor Node Metastasis (TNM) stage using discriminant indices.ResultsA total of 736 patients with rectal cancer were included in the study. ACR was significantly higher in patients with poor survival or cancer recurrence. A low ACR was associated with increased tumor invasiveness, longer hospital stays, and higher hospitalization costs. Patients with a high ACR had significantly better PFS (62.9% vs. 35.2%, p < 0.001) and OS (67.0% vs. 37.2%, p < 0.001) than those with a low ACR. ACR can serve as an effective auxiliary tool for pathological staging, especially in patients with stage III–IV disease. The relationship between ACR and mortality risk was L-shaped. ACR is an independent prognostic factor for PFS [HR = 0.581, 95% confidence interval (CI): 0.458–0.738, p < 0.001] and OS (HR = 0.560, 95% CI: 0.435–0.720, p < 0.001) in rectal cancer patients. ACR-based nomograms have good predictive accuracy and outperform traditional TNM stage in predicting prognosis.ConclusionAlbumin–carcinoembryonic antigen ratio is a simple and effective clinical tool for predicting the recurrence and survival of patients with rectal cancer and is a useful supplement to the TNM stage.